Recurrent atraumatic subdural hematoma with pregnancy – An unusual case - Dasgupta, Sibaji; Guria, Sourabh (Asian Journal of Medical Sciences, 2022)
Atraumatic subdural hematoma (SDH) is a rare occurrence in neurosurgery practice. Such a case in pregnancy is also very rare. Here, we present a case of 33 weeks pregnant female presented with SDH which was operated and there was recurrence of similar hematoma in the same patient in the postpartum period. The primary cause in both the hematomas was unknown, but a pregnancy related or other risk factors may be responsible for causation of the hematomas in this case.